A High-Sensitivity Resonant Magnetic Sensor Based on Graphene Nanomechanical Resonator - Wenyao Liu; Wei Li; Chenxi Liu; Enbo Xing; Yanru Zhou; Lai Liu; Jun Tang (Micromachines, 2022)
This paper presents a novel resonant magnetic sensor consisting of a graphene nanomechanical oscillator and magnetostrictive stress coupling structure, using Si/SiO2 substrate and Fe–Ga alloy, respectively. In this device, the deformation of the Fe–Ga alloy resulting from the external magnetic field changed the surface tension of the graphene, resulting in a significant change in the resonance frequency of graphene. Using the finite element analysis, it could be found that the response of the resonance frequency revealed a good linear relationship with the external magnetic field (along the x-axis) in the range of the 1 to 1.6 mT. By optimizing the sizes of each component of the magnetic sensor, such as the thickness of the Si/SiO2 substrate and the Fe–Ga alloy, and the length of the graphene, the sensitivity could even reach 834 kHz/mT, which is three orders of magnitude higher than conventional resonant magnetic devices. This provides a new method for highly sensitive and miniaturized magnetic sensors.